Mangrove Seeds and Their Role in Climate Adaptation and Coastal Ecosystem Management - SADR UL ANAM; ABDUL KAREEM VETTAN; POOJA SURESH; JASMIN LAILA RASHEED (Seed Research, 2025)
Mangroves represent specialized coastal ecosystems that play a crucial role in shoreline stabilization,carbon storage, and biodiversity conservation. Their seeds and propagules possess unique physiological andmorphological adaptations that enable successful germination and establishment under saline and waterloggedconditions. Understanding these biological traits is essential for developing efficient propagation and restorationstrategies. This article examines the seed biology of mangroves, the environmental parameters influencing theirgermination, and practical approaches for seed handling and establishment. Methods including pre-sowingtreatments, nursery techniques, and recent innovations such as drone-assisted dispersal are discussed withreference to their application in the United Arab Emirates. By integrating conventional and advanced propagationmethods, the study highlights the importance of mangrove seed-based approaches in enhancing restorationsuccess and contributing to climate-resilient coastal management.